ANALISIS NIAT PENGGUNAAN ARTIFICIAL INTELLIGENCE TOOLS OLEH PELAJAR DALAM SEKTOR PENDIDIKAN - Radhia, Fathy; Aini, Nurul; Afrilia, Nur Sitha (ISTEK WIDURI, 2023)
Technology today has a very significant influence on all sectors of life. This is marked by the Industrial Revolution 4.0. In the world of education, this is certainly a matter of great concern. Technological developments that occur can be a tool for teachers and students to carry out learning and teaching activities. The technology in question is the presence of Artificial Intelligence (AI). Currently, AI is experiencing an increase in its use. Students in various levels of education are active users of technology, so AI has enormous potential to play a significant role now and in the future. This study aims to determine the intention to use AI tools among students from various educational levels, such as elementary, junior high, high school, undergraduate, graduate, and doctoral. The research method used in this research is quantitative method, where this research distributes questionnaires using Microsoft Form with respondents who are students from various levels of education and have used AI tools in the learning process. The model used in this study uses the Technology Acceptance Model (TAM) model. This study shows that the Trust variable has no effect on Attitude Toward Using. This can be seen from the t-test value of less than 1.97, namely 1.623 and a p-value of more than 0.05, namely 0.105. Future research is recommended to be able to add other variables, use other research models, and be able to classify the level of education.